2020
DOI: 10.1007/s00167-020-06276-y
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal allograft transplantation in The Netherlands: long-term survival, patient-reported outcomes, and their association with preoperative complaints and interventions

Abstract: Purpose Evaluation of survival of meniscal allograft transplantation (MAT) and postoperative patient-reported outcome (PRO), and their association with prior interventions of the knee. Methods A prospective consecutive study of 109 consecutive patients who had an arthroscopic meniscal allograft transplantation (MAT) between 1999 and 2017 by a single surgeon. Patients were assessed with KOOS scores, preoperative and after a minimal follow-up of 2 years. Furthermore, two anchor questions (whether expectations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 30 publications
(43 reference statements)
3
28
0
Order By: Relevance
“…28,35 Reported 10-year survivorship for cryopreserved allografts range from 45% to 90.3%, although definitions of failure used in the various studies are heterogeneous. 11,31,32 When compared with survivorship across all graft preparation and surgical techniques with long-term follow-up, the present study reports higher survivorship than the 10-year survival rate of 73.5% reported by Novaretti et al 20…”
Section: Discussionsupporting
confidence: 43%
“…28,35 Reported 10-year survivorship for cryopreserved allografts range from 45% to 90.3%, although definitions of failure used in the various studies are heterogeneous. 11,31,32 When compared with survivorship across all graft preparation and surgical techniques with long-term follow-up, the present study reports higher survivorship than the 10-year survival rate of 73.5% reported by Novaretti et al 20…”
Section: Discussionsupporting
confidence: 43%
“…Meniscal allografting, an alternative treatment for isolated lateral compartment knee pain, has shown positive results; however, outcomes and survivorship are dependent on the severity of arthritis and the age of the patient 11 . van der Wal et al reported a decline in mean KOOS ADL and Sport subscores over time, with scores of <60 between 2 and 4 years and scores of <40 by year 6 11. In our cohort of patients who were managed with lateral UKA, the KOOS ADL subscore was 91 and the KOOS Sport subscore was ≥70 at mean of 10 years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…increase in progression of lateral OA 3 . Treatment options for isolated lateral compartment OA in patients <60 years of age more commonly include cartilage procedures, meniscal transplants, and femoral osteotomies [5][6][7][8][9][10] ; however, these options can be less favorable because of limited longevity, restriction of activities and sports participation 5,7,[9][10][11] , and complications such as infection, venous thromboembolism, fracture, delayed union or nonunion, and implant failure 6,8 .…”
mentioning
confidence: 99%
“…However, the current knowledge of MAT survivorship is limited, the main limitation being the small cohorts studied, which rarely exceed 100 patients. 26 A few larger case series reported survival analysis and outcome, especially of the bony fixation technique. 17 , 25 The mean survival rates ranged from 11 years 24 , 28 to 16.1 years, 26 and each study proposed different criteria to define failure 18 : some definitions were based on clinical outcome and knee function alone, and others relied on a patient’s need for reoperation, although without consensus on the kind of outcomes considered to indicate failure.…”
mentioning
confidence: 99%